Determinants of iron-rich food deficiency among children under 5 years in sub-Saharan Africa: a comprehensive analysis of Demographic and Health Surveys - Emmanuel Osei Bonsu; Isaac Yeboah Addo; Elijah Frimpong Boadu; Caleb Boadi; Sylvester R Okeke (BMJ Open)
Background Iron deficiency is a major public health problem that affects the physical and cognitive development of children under 5 years of age (under-5 children) in sub-Saharan Africa (SSA). However, the factors associated with the limited consumption of iron-rich foods in the region are poorly understood.Objective This study examined the prevalence and determinants of iron-rich food deficiency among under-5 children in 26 SSA countries.Design This nationally representative quantitative study employed pooled data from Demographic and Health Surveys conducted between 2010 and 2019.Methods Representative samples comprising 296 850 under-5 children from the various countries were used. Bivariate and multivariate logistic regression models were used to determine the associations between the lack of iron-rich food uptake and various sociodemographic factors.Result The overall prevalence of iron-rich food deficiency among the children in the entire sample was 56.75%. The prevalence of iron-rich food deficiency varied widely across the 26 countries, ranging from 42.76% in Congo Democratic Republic to 77.50% in Guinea. Maternal education, particularly primary education (OR 0.62, 95% CI 0.57 to 0.68) and higher education (OR 0.58, 95% CI 0.52 to 0.64), demonstrated a reduced likelihood of iron-rich food deficiency in the sample. Likewise, paternal education, with both primary education (OR 0.69, 95% CI 0.63 to 0.75) and higher education (OR 0.66, 95% CI 0.60 to 0.73) showed decreased odds of iron-rich food deficiency. Postnatal visits contributed significantly to reducing the odds of iron-rich food deficiency (OR 0.90, 95% CI 0.83 to 0.95), along with antenatal visits, which also had a positive impact (OR 0.84, 95% CI 0.74 to 0.95). Finally, residents in rural areas showed slightly higher odds of iron-rich food deficiency (OR 1.12, 95% CI 1.10 to 1.28).Conclusion Based on the findings, interventions targeting iron-food deficiency in the SSA region should take into strong consideration the key determinants highlighted in this study.